Critical Land Detection Watershed River Bengkulu and Effect of Coastal Area using Geographic Information System - Supriyono, Supriyono (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The specific objective research to detect changes in land for the detection of critical areas and its effect on coastal areas with spatial approach. Determining the change detection of critical areas and coastal areas with Landsat image analysis. The approach used in this study based spatial modeling and then conducted a field survey/matching analysis results with physical characteristics of the land, so that will be obtained data is detection of critical land area and its impact coastal areas. The approach will be analyzed aerial photographs image interpretation and processing of spatial data using geographic information system (GIS). The results of the study are (1) changes in critical land area is 1990 to 240.824 ha or equal 8.384%, in 2005 to 306.202 ha or at 10.661%, in 2015 to 1114.189 ha or by 38.791% and in 2016 with 1211.084 ha or equivalent to 42.164% of the total area of ​​2872.299 ha. and (2) physical Condition Texture critical land and soil structure to be damaged by coal mining and (3) influence coastal areas their physical shape changes occur in the vast river, meanders and estuaries Bengkulu River watershed are caused by the erosion and deposition rate as a result of coal mining upstream part of the river and waste coal mining activities along the riverbanks.